Information Security and Privacy: Networking Challenges Policy in the Digital World - Derevianko, Olena (Decision, 2024)
Information security and privacy issues are growing more difficult in the quickly evolving digital era. This article examines the critical role of policy networks in tackling these issues. We provide a thorough understanding of information security, digital privacy, and the legislative complexities that surround digital regulations. The primary focus is on modern information security risks such as malware, ransomware, and identity theft, as well as how policy networks can be used to coordinate solutions. Regulatory complexity, inter-agency collaboration, and stakeholder involvement are among the issues addressed. Case studies and lessons from policy implementation provide specific insights into the effectiveness of policy network activities. The conclusion highlights major results and practical implications for improving digital information security and privacy, with a focus on interagency collaboration and raising awareness. This study adds to our understanding of the critical role of policy networks in addressing the dynamics of information security and privacy in the digital age.